SISTEM PAKAR DIAGNOSA PENYAKIT PADA IBU HAMIL BESERTA PENANGANANNYA DENGAN METODE FORWARD CHAINING DAN CERTAINTY FACTOR BERBASIS WEB - Marshall Anugrah Najmi (2023)
Pregnancy process reduces the body's immunity, making it susceptible to diseases during pregnancy. This is one of the causes of the high Maternal Mortality Rate (MMR) in Indonesia. The high death rate is due to a lack of knowledge about pregnancy-related symptoms, resulting in delayed appropriate actions. Technological advancements provide benefits in various fields, including healthcare. This expert system application aims to identify diseases in pregnant women using forward chaining and certainty factor methods. The system utilizes information from interviews, internet sources, and book references to diagnose pregnancy-related diseases. The ultimate goal is to draw conclusions about the pregnancy disorders experienced by pregnant women. The results obtained after designing this expert system showed an accuracy percentage of 85.7%, diagnosing 21 types of diseases in pregnant women along with their 34 symptoms. This research is expected to provide knowledge regarding pregnancy-related diseases based on their symptoms.